In-hospital Outcomes of Primary Percutaneous Coronary Intervention (PCI) Using a Transradial Technique - Ibrahim Shah, Samiullah Khan, Umar Ibrahim Paracha, Saif Ullah, Matiullah Khan, Akhtar Sher, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Patients suffering from ST-elevation myocardial infarction (STEMI) are preferably treated with primary percutaneous coronary intervention (PCI). Despite the anterior femoral approach having historically been the vascular access of choice, the transradial approach is more commonly preferred because of its lower complication rates for the patient. This study sought to assess the in-hospital outcomes of performing primary PCI through the transradial approach in ‘patients diagnosed with STEMI’. Methods: A descriptive observational study was conducted at two cardiac care centers, Mohamad Sardar Memorial Hospital, Swabi, and the Pak Welfare Cardiac Cath Lab, Pak Medical Center and Hospital, Peshawar. The study population comprised of 105 participants who underwent transradial primary PCI between March 2022 and May 2023. These patients’ demographics, clinical history, procedural details, and in-hospital outcomes were collected and analyzed. Results: The study highlighted an exceptional achievement in procedural success, standing at 96.2%. While there was a complication at the access site in 1.9% of patients, the rate of major hemorrhage was below 1%. Other complications like acute kidney injury (3.8%), arrhythmias (6.7%), and reinfarction (1.9%) were also exceptionally low. The rate of death in the hospital was low at 2.9%. This data demonstrates the appropriate safety profile for the transradial approach in compensatory cases. Conclusion: Using the transradial artery for primary PCI intervention in STEMI patients is effective and uncomplicated. As an approach to urgent cardiac procedures, it achieves excellent results while maintaining a low complication rate. These findings add to the growing literature supporting the use of the transradial technique for effective coronary intervention. Keywords: STEMI, primary PCI, transradial access, in-hospital outcomes, coronary intervention, vascular complications.